Odors enhance the salience of matching images during the attentional blink - Robinson, Amanda K.; Mattingley, Jason B.; Reinhard, Judith (Frontiers in Integrative Neuroscience, 2013)
As any food critic knows, the visual presentation of a dish can enhance its aroma. Is the reverse also true? Here we investigated whether odors can enhance the salience of familiar visual objects at the limits of perceptual discrimination, using rapid serial visual presentations (RSVP) to induce an attentional blink (AB). We had participants view RSVP streams containing photographs of odor-related objects (lemon, orange, rose and mint) amongst non-odor related distractors. In each trial, participants inhaled a single odor, which either matched the odor-related target within the stream (congruent trials), did not match the odor-related target (incongruent trials), or was irrelevant with respect to the target. Congruent odors significantly attenuated the AB for odor-related visual targets, compared with incongruent and irrelevant odors. The findings suggest that familiar odors can render matching visual objects more salient, thereby enhancing their competitive strength at the limits of temporal attention.